2020
DOI: 10.1038/s41598-020-67888-5
|View full text |Cite
|
Sign up to set email alerts
|

Clinical efficacy of eyelid hygiene in blepharitis and meibomian gland dysfunction after cataract surgery: a randomized controlled pilot trial

Abstract: The purpose of this randomized clinical trial is to evaluate the effect of eyelid hygiene on subjective symptoms, anterior blepharitis, and meibomian gland dysfunction (MGD) after cataract surgery. Subjects with obstructive MGD who underwent cataract surgery were randomly divided into two groups. In the eyelid hygiene group, eyelid hygiene was performed twice a day for 10 days from 3 days before to 1 week after cataract surgery. The control group did not perform eyelid hygiene. A subjective symptom questionnai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 44 publications
(70 reference statements)
0
20
2
Order By: Relevance
“…The results revealed that the microbiota of the eyelid margin and conjunctiva were influenced by each other, which could explain why blepharitis tends to cause ocular surface inflammation such as conjunctivitis, keratitis, and even postoperative infection after inner eye surgery such as cataract surgery. It also reminds clinicians to pay attention to the health of eyelid margins when diagnosing and treating ocular surface inflammation or before intraocular surgery ( 44 47 ).…”
Section: Discussionmentioning
confidence: 99%
“…The results revealed that the microbiota of the eyelid margin and conjunctiva were influenced by each other, which could explain why blepharitis tends to cause ocular surface inflammation such as conjunctivitis, keratitis, and even postoperative infection after inner eye surgery such as cataract surgery. It also reminds clinicians to pay attention to the health of eyelid margins when diagnosing and treating ocular surface inflammation or before intraocular surgery ( 44 47 ).…”
Section: Discussionmentioning
confidence: 99%
“…It had been reported that cataract surgery can worsen blepharitis and meibomian gland function during the postoperative period to result in increased ocular discomfort and decreased vision and patient satisfaction 6 11 . However, most of these reports describe posterior blepharitis/MGD and little is known about anterior blepharitis after cataract surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the improved surgical outcomes and extremely elevated patient expectations in recent cataract surgery, postoperative discomfort is often a major disappointment to the patients 6 . As stated earlier, MGD (posterior blepharitis) involvement in postoperative discomfort after cataract surgery is well documented.…”
Section: Introductionmentioning
confidence: 99%
“…MGD can be considered a cause of posterior blepharitis and evaporative dry eye, resulting in excess free cholesterol and cholesterol esters in tears [ 43 , 44 , 45 , 46 ]. Changes in tear composition disrupt the meibum layer, resulting in inflammatory cell infiltration of the ocular surface epithelium, along with an increase in the expression of proinflammatory cytokines including IL-1β, IL-6, IL-17, IFN-γ, tumor necrosis factor (TNF)-α, and matrix metalloproteinase (MMP)-9 [ 47 , 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%